Biofortification and phytoremediation of selenium in China - Wu, Zhilin; Bañuelos, Gary S.; Lin, Zhi-Qing; Liu, Ying; Yuan, Linxi; Yin, Xuebin; Li, Miao (Frontiers in Plant Science, 2015)
Selenium (Se) is an essential trace element for humans and animals but at high concentrations, Se becomes toxic to organisms due to Se replacing sulfur in proteins. Selenium biofortification is an agricultural process that increases the accumulation of Se in crops, through plant breeding, genetic engineering, or use of Se fertilizers. Selenium phytoremediation is a green biotechnology to clean up Se-contaminated environments, primarily through phytoextraction and phytovolatilization. By integrating Se phytoremediation and biofortification technologies, Se-enriched plant materials harvested from Se phytoremediation can be used as Se-enriched green manures or other supplementary sources of Se for producing Se-biofortified agricultural products. Earlier studies primarily aimed at enhancing efficacy of phytoremediation and biofortification of Se based on natural variation in progenitor or identification of unique plant species. In this review, we discuss promising approaches to improve biofortification and phytoremediation of Se using knowledge acquired from model crops. We also explored the feasibility of applying biotechnologies such as inoculation of microbial strains for improving the efficiency of biofortification and phytoremediation of Se. The key research and practical challenges that remain in improving biofortification and phytoremediation of Se have been highlighted, and the future development and uses of Se-biofortified agricultural products in China has also been discussed.